2017
DOI: 10.2174/1389202917666160803162309
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Phytometabolites Targeting Cancer Stem Cells

Abstract: Medicinal plants are a plentiful source of bioactive molecules with much structural diversity. In cancer treatment, molecules obtained from plants represent an attractive alternative to other treatments because several plant-derived compounds have exhibited lower toxicity and higher selectivity against cancer cells. In this review, we focus on the possible application of bioactive molecules obtained from plants against more primitive cell populations in cancers, cancer stem cells. Cancer stem cells are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 228 publications
(246 reference statements)
1
20
0
1
Order By: Relevance
“…Another vitamin E tocotrienol isomer, γ-TT, was reported to specifically target the CSC subpopulation in different cancer cells (colorectal, breast, prostate) 57 60 . This ability to counteract tumor growth by targeting both the bulk tumor cells and the CSC subpopulation has previously been reported for other natural compounds 21 – 25 .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Another vitamin E tocotrienol isomer, γ-TT, was reported to specifically target the CSC subpopulation in different cancer cells (colorectal, breast, prostate) 57 60 . This ability to counteract tumor growth by targeting both the bulk tumor cells and the CSC subpopulation has previously been reported for other natural compounds 21 – 25 .…”
Section: Discussionsupporting
confidence: 74%
“…Based on their key role in the mechanisms of drug resistance, CSCs are now considered a promising effective target for novel therapeutic strategies for cancer 11 , 12 . So far, several compounds, both synthetic and natural, have been reported to exert a significant antitumor activity by targeting cancer ‘stemness’, besides decreasing the viability of the bulk population of cells, in different types of tumors 25 , 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of pathways essential for modulating stemness properties has contributed to the identification of several molecules that could eliminate GSCs, including new antineoplastic agents from natural sources [106][107][108][109][110][111][112][113]. A summary of current potential treatments is presented in Table 1 and Fig.…”
Section: Current Strategies Targeting Cancer Stem Cellsmentioning
confidence: 99%
“…Recent evidence has shown that cancer stem cells undergo continuous mutations and are responsible for drug resistance and relapse. Targeting cancer stem cells is challenging, but identifying drugs which can work on stem cells can solve the relapse and resistance seen in most of the high-grade tumors [7].…”
Section: Introductionmentioning
confidence: 99%